Is Maternal Methadone Dose Associated with the Severity of Neonatal Abstinence Syndrome? - Smith, Jessica; Lafferty, Margaret; Boelig, Rupsa C.; Carola, David; Adeniyi-Jones, Susan; Kraft, Walter K.; Greenspan, Jay S.; Aghai, Zubair H. (American Journal of Perinatology, 2020)
Objective The aim of the study is to assess the correlation between maternal methadone dose and severity of neonatal abstinence syndrome (NAS) in infants that required pharmacological treatment for NAS.Study Design This is a retrospective analysis of 574 infants ≥35 weeks' gestation exposed to methadone in utero, born between August 2006 and May 2018, and who required pharmacological therapy for NAS. Indicators of NAS severity (duration of morphine treatment, maximum morphine dose, use of phenobarbital, and length of hospitalization) were compared between infants exposed to high (≥200 mg), intermediate (100–199 mg), and low doses (<100 mg) of methadone. Logistic and linear regression models were used to adjust for the covariates.Results Median (interquartile range) duration of medical treatment with morphine was higher in infants exposed to higher doses of methadone (low dose 23 [14–37] days, intermediate dose 31 [18–45] days, and high dose 35 [20–48] days, p < 0.001). Higher methadone doses were also predictive of longer duration of hospitalization, higher maximum morphine dose, and increased likelihood of treatment with phenobarbital. The association between maternal methadone dose and the severity of NAS persisted in multivariable regression models.Conclusion Infants exposed to higher methadone doses displayed more severe NAS, as indicated by longer durations of treatment, higher maximum morphine dose, longer duration of hospitalization, and increased likelihood of phenobarbital use.Key Points
Keywords: NICU; SSRI; withdrawal; morphine; NAS